PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA PADA MATERI BENTUK DAN OPERASI BILANGAN PECAHAN MELALUI MODEL PEMBELAJARAN RESITASI PLUS SNOWBALL THROWING DI KELAS VII – 2 MTs.YPKS PADANGSIDIMPUAN T.A 2020-2021 - lubis, yulia rizka; makmur, agus; Harahap, adek nilasari (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2021)
This research aims to find out the great improvement of students' creative thinking skills through the Recitation Plus Snowball Throwing learning model of material mathematics Learning Form and Operation of Fractional Numbers in grades VII-2 MTs YPKS Padangsidimpuan Year 2020/2021. This type of research is Class Action Research (PTK) consisting of 2 Cycles. The subject of the study was class VII-2 of 20 people. Women as many as 10 men and 10 men. The object taken in this study is the use of the Recitation Plus Snowball Throwing learning model in an effort to improve students' creative mathematical thinking skills on the subject of Fractional Number Form and Operation. The results showed that the results of the student's creative thinking skills test by applying the Recitation Plus Snowball Throwing learning model with a minimum assessment criteria of